Family meal participation is associated with dietary intake among 12-month-olds in Southern Norway - Elisabet R. Hillesund; Linda R. Sagedal; Elling Bere; Nina C. Øverby (BMC, 2021)
Abstract Background Family meal participation is associated with healthier eating among children and adolescents. Less is known about family meal participation among infants and toddlers. The objective of the present study was to explore whether family meal participation at 12 months of age is associated with dietary intake and whether a potential relationship differs according to maternal education or child sex. Methods Follow-up data from children born to mothers participating in the Norwegian Fit for Delivery (NFFD) trial during pregnancy were used to assess the frequency of intake of 11 dietary items according to frequency of participating in the respective family meals. Dietary differences according to seldom (0-3 times/week) or often (4-7 times/week) participating in each respective meal category were assessed in linear regression models. Potential dose-response associations with frequency of participation in all family meal categories combined were also estimated. Models were adjusted for maternal randomization status, education, and child sex. Results The sample comprised 408 children. A total of 74, 53 and 74% had breakfast, lunch, and dinner with family ≥4 times/week, respectively, while 39% had supper and 27% between-meal snacks with family ≥4 times/week. Having family dinner ≥4 times/week was associated with more frequent intake of vegetables, homemade infant cereal, milk, and water, and less frequent intake of commercial infant foods while the other family meal categories were associated with fewer dietary outcomes. For each additional meal category eaten with family ≥4 times/week, frequency of vegetable intake (β = 0.45), water (β = 0.17), and milk (β = 0.09) per day increased, while commercial infant cereal was eaten less frequently (β = − 0.18). The inverse association between family meals and commercial infant cereal was only evident in children born to mothers in the intervention group. Several associations with diet were stronger and only significant among boys. Conclusions Being fed in the context of family meals at 12 months of age was associated with a more favorable diet. Including the infant in family meals has potential in the promotion of early nutritional health.